Expresive Illocutionary Acts in Disney + Luca Film : A Pragmatic Analysis - Cep Ruly M Cahyana; Ervina CM Simatupang (Universitas Cokroaminoto Palopo, 2024)
This pragmatic study investigates the importance of expressive illocutionary acts in character and plot development in the movie Luca from Disney+. By analyzing dialogue from the movie, this study identifies and examines various instances of expressive illocutionary acts, including thanking, praising, complaining, apologizing, and blaming. Using the descriptive-qualitative method, a total of expressive illocutionary acts are identified, which include 5 examples of thanking, 1 example of praising, 1 example of complaining, 1 example of apologizing, and 1 example of blaming. These speech acts were further analyzed for their underlying functions, ranging from competitive purposes to friendly, collaborative, and conflictual purposes. The objective of this research is to explore how expressive illocutionary acts contribute to the emotional depth of the characters and to the resolution of conflicts within the plot. Through this classification, we gain a deeper understanding of how these communicative acts function to reinforce social norms, negotiate conflict, and shape the overall storyline